Theory-Praxis: Principals vs. Agents among Namibian Public Enterprises - Ralph Marenga (iRASD Journal of Management)
In Namibia, public enterprise (PE) agents are obligated to prioritize and advance the interests of their principals (namely the government). However, recent trends have seen the proliferation of conflicts arising due to impediments such as information asymmetry, misaligned incentives, and political interference in the management of PEs. These impediments have the tendency to contradict the positive expected standards of accountability and result in a negative disconnect with the principles of the agency theory. The overall lackluster results and performance of PEs in Namibia suggest that some alignment to the positive expectations of the agency theory, while deviations are also observed in the management of PEs. Qualitative research approach was used in this study to analyze secondary data through thematic analysis, interpretivism and theory deduction. The analysis of data led to findings that show that PEs in Namibia struggle with accountability, transparency and performance-driven incentives as outlined by the agency theory. Political influence in the management of PEs was also found to continually skew essential decision-making processes. This misaligns the actions of PE agents with the true interests of the principals via the agency theory. Challenges such as information asymmetry and weak governance frameworks hinder the principal’s (government’s) ability to oversee PE performance, thereby reducing agency. Addressing the above agency challenges (by reducing political interference, rigorously applying governance frameworks, establishing performance-based incentives, strengthening board autonomy, ensuring personal accountability, and enforcing transparency) in PEs has the prospect to significantly improve agency relationships in Namibian PEs, thereby reducing agency loss.